Effects of exercise in a relapsing‐remitting model of experimental autoimmune encephalomyelitis. Issue 10 (17th June 2016) - Klaren, Rachel E.; Stasula, Ulana; Steelman, Andrew J.; Hernandez, Jessica; Pence, Brandt D.; Woods, Jeffrey A.; Motl, Robert W.
Abstract : Previous research has examined the effects of exercise in experimental autoimmune encephalomyelitis (EAE), the animal model of multiple sclerosis. However, all previous studies have utilized a chronic model of EAE, with exercise delivered prior to or immediately after induction of EAE. To our knowledge, no study has examined the effects of exercise delivered during a remission period after initial disease onset in a relapsing‐remitting model of EAE (RR‐EAE). The current study examines the effects of both voluntary wheel running and forced treadmill exercise on clinical disability and hippocampal brain‐derived neurotrophic factor (BDNF) in SJL mice with RR‐EAE. The results demonstrate no significant effects of exercise delivered during remission after initial disease onset on clinical disability scores or levels of hippocampal BDNF in mice with RR‐EAE. Furthermore, our results demonstrate no significant increase in citrate synthase activity in the gastrocnemius and soleus muscles of mice in the running wheel or treadmill conditions compared with the sedentary condition. These results suggest that the exercise stimuli might have been insufficient to elicit differences in clinical disability or hippocampal BDNF among treatment conditions. © 2016 Wiley Periodicals, Inc. Abstract : The novel findings of this study demonstrate no significant effects of exercise delivered during remission after the initial disease onset on clinical disability in mice with a relapsing‐remitting model of experimental autoimmune encephalomyelitis (EAE).